Problematika dan Tantangan Desentralisasi di Indonesia: Kajian Literatur Review Pasca Reformasi - Srisaparmi, Srisaparmi; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
Post-1998 reform decentralization in Indonesia has become a major strategy in strengthening regional autonomy and accelerating development through the delegation of authority from the central government to the regions. Although it aims to increase public participation and service quality, its implementation faces various structural, cultural, and policy challenges. This study aims to fill the gap in studies that have not integrated these three dimensions comprehensively, especially in the context of authority conflicts and capacity disparities between regions. This study uses a qualitative approach with the systematic literature review (SLR) method, analyzing various scientific literature, regulations, and policy reports from 1998 to 2024. The results of the study show that decentralization has not been fully effective due to the high fiscal inequality, weak institutional capacity, and minimal harmonization of central-regional policies. On the other hand, several regions have succeeded in presenting public service innovations thanks to progressive local leadership. The conclusion of this study emphasizes the need for further reforms in the form of increasing the capacity of regional institutions, harmonizing regulations, and strengthening participatory oversight mechanisms. These findings not only enrich theoretical understanding of decentralization, but also provide applicable and contextual policy recommendations for more effective and sustainable regional governance.